Symmetric continuous linear functionals on complex space L_∞[0,1] - Vasylyshyn, T.V. (Carpathian Mathematical Publications, 2014)
We prove that every symmetric continuous linear functional on the complex space L_∞[0,1] can be represented as a Lebesgue integral multiplied by a constant.